A new method for wheel–rail contact force continuous measurement using instrumented wheelset. Issue 2 (1st February 2019) - Ren, Yu; Chen, Jianzheng
ABSTRACT: With the aim of improving the continuous measurement of wheel–rail contact force by instrumented wheelset, instead of solving the non-linear equations, we proposed a new method based on state space theory. With this new method, the wheel–rail contact force can be calculated by the recurrence relation and the signals from strain gauge bridges on wheel web. The implementation of continuous instrumented wheelset is quite general and simplified, due to the specific bridging scheme is not necessary. It means that continuous measurement of the contact force could be realised with a simple bridging scheme, even as simple as discrete instrumented scheme. In this work, we first demonstrated and discussed the effectiveness and accuracy of this new method by estimation results with the numerical simulations, and we also applied this new method to two field tests, including one was conducted in a loop test line using a high-speed train and the other one was conducted in an urban line with a light rail vehicle. In a word, this new method is proved to be an effective way to monitor the wheel–rail contact force of rail vehicle track system.